2021
DOI: 10.1016/j.heliyon.2021.e06403
|View full text |Cite
|
Sign up to set email alerts
|

A case study of the relationship between smallholder farmers' ICT literacy levels and demographic data w.r.t. their use and adoption of ICT for weather forecasting

Abstract: Food insecurity caused by climate change has become one of the main issues on the global agenda. Worldwide, the importance of digital tools as a means to enhance adaptive capacity and resilience of smallholder farmers (SHFs) in the face of climate variability has long been recognised. Technology-based systems in agriculture frequently neglect to consider the actual context of use and adoption by SHFs in rural and developing contexts. These conditions, as pointed out in the literature, range from high "illitera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
1
4
0
2
Order By: Relevance
“…Krell et al (2020) investigated smallholder farmer's use of mobile phone services in central Kenya and found that some of the factors affecting the adoption of such services are related to literacy levels and the cost of technology. Alant & Bakare (2021), in their study to establish the relationship between smallholder farmers' literacy levels and use of ICTs, agreed with the above findings. Their study established that farmers with low levels of literacy failed to display various ICT related skills such as decoding symbols on the phone, accepting and terminating a call, increasing and decreasing volume on the phone and identifying a caller in the case of a missed call.…”
Section: Factors Affecting Adoption Of Ict Among Farmerssupporting
confidence: 66%
“…Krell et al (2020) investigated smallholder farmer's use of mobile phone services in central Kenya and found that some of the factors affecting the adoption of such services are related to literacy levels and the cost of technology. Alant & Bakare (2021), in their study to establish the relationship between smallholder farmers' literacy levels and use of ICTs, agreed with the above findings. Their study established that farmers with low levels of literacy failed to display various ICT related skills such as decoding symbols on the phone, accepting and terminating a call, increasing and decreasing volume on the phone and identifying a caller in the case of a missed call.…”
Section: Factors Affecting Adoption Of Ict Among Farmerssupporting
confidence: 66%
“…Data literacy at the end-user level is also closely related to ICT (Information and Communication Technology) literacy, which is defined as using "digital technology, communication tools, and or networks to access, manage, integrate, evaluate, and create information in order to function in a knowledge society." This definition mirrors the conceptualization of data literacy used in the present study [17].…”
Section: Three Levels Of Literacymentioning
confidence: 62%
“…For example, some studies have shown that 2% of the total greenhouse gas emissions by the information technology industry is almost equal to that of the aviation industry. Also, very large data centres around the world can consume as much energy as a large city [65,66].…”
Section: Effective Economic Methodsmentioning
confidence: 99%